2018
DOI: 10.1186/s12943-017-0756-y
|View full text |Cite
|
Sign up to set email alerts
|

STAT3-induced lncRNA HAGLROS overexpression contributes to the malignant progression of gastric cancer cells via mTOR signal-mediated inhibition of autophagy

Abstract: BackgroundLong noncoding RNAs (lncRNAs) are an important class of functional regulators involved in human cancers development, including gastric cancer (GC). Studying aberrantly expressed lncRNAs may provide us with new insights into the occurrence and development of gastric cancer by acting as oncogenes or tumor suppressors. In this study, we aim to examine the expression pattern of lncRNA HAGLROS in GC and its clinical significance as well as its biological role in tumor progression.MethodsBioinformatics ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
161
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(168 citation statements)
references
References 39 publications
7
161
0
Order By: Relevance
“…In contrast, LINC00319 is down‐regulated with age and promotes tumor growth via transcriptional silencing (Zhang et al, ). Given the emerging evidence that lncRNAs help direct mTOR specificity in vitro (Chen et al, ; Li et al, ), this suggests that our age‐regulated lncRNAs can fine‐tune the regulation of longevity‐related proteins.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, LINC00319 is down‐regulated with age and promotes tumor growth via transcriptional silencing (Zhang et al, ). Given the emerging evidence that lncRNAs help direct mTOR specificity in vitro (Chen et al, ; Li et al, ), this suggests that our age‐regulated lncRNAs can fine‐tune the regulation of longevity‐related proteins.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, no study has utilized technology to both measure exon‐specific transcript signals and provide robust coverage of tissue long noncoding RNAs (lncRNAs, 50% of the human transcriptome; Timmons et al, ; Deveson, Hardwick, Mercer, & Mattick, ). Furthermore, emerging evidence demonstrates that lncRNAs can modulate mTOR activity (Chen et al, ; Li et al, ). These factors could combine to explain why existing models of human aging do not consistently identify a molecular program dominated by the canonical regulators of longevity in nonhuman systems.…”
Section: Introductionmentioning
confidence: 99%
“…Two overlapping epitopes were identified in lncRNA HAGLROs, which were expressed and presented only in the lung tumor tissue. This lncRNA has been implicated in cancer progression 60,61 and should now be prioritized for downstream validation. Moreover, while Laumont et al 24 first proposed the existence of shared noncHLAIp, our work validates that noncHLAIp can be shared across multiple tumor samples and thus we anticipate greater efficiency in treatment with such shared noncHLAIp compared to private neoantigens 62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…**p < 0.01, vs. control; ## p < 0.01, vs. ALI+vehicle; $ p < 0.05, $$ p < 0.01, vs. ALI+NCI-MVs 100 inhibition by miR-100 inhibitor aggravated the LPSinduced cell injury and inhibited LPS-induced autophagy in LPS-treated WI-38 human lung fibroblasts, a cell model of pulmonary injury [15]. The regulation of autophagy by miR-100 has been examined by several studies [26,27]. For example, Yu et al reported that in osteosarcoma, miR-100 upregulation enhanced cell autophagy and apoptosis induced by cisplatin via targeted inhibiting of mTOR, which was known to be an important negative signal of autophagy [28].…”
Section: Discussionmentioning
confidence: 99%